Built up : an historical perspective on the contemporary principles and practices of real estate development - Derrington, Patrice (New York, NY : Routledge/Taylor & Francis Group, 2021)
"Built Up uncovers the roots of the global real estate industry in the machinations of a patron of Shakespeare, the merged lineages of business savvy women and men, startlingly innovative collaborations with the first English architect, and the radical explorations of other denizens of early modern London-and what those colorful origins mean for the practice of property development today. Uniting insights from the author's career as an internationally recognized developer with meticulous archival research, this resource for scholars and professionals synthesizes economic history and the latest planning and finance literature"--
OCLC-licensed vendor bibliographic record.
Keywords: Real estate business -- England -- London -- History; Read estate business; Real estate development -- England -- London -- History; Real estate development -- History; BUSINESS & ECONOMICS / Real Estate; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; BUSINESS & ECONOMICS / Economic History